Covering a billion with DOTS : my experiences with India's revised TB control programme (1998-2004) - Gupta, Deepak (Delhi, 2005)
The authors of the recently published India Health Report, which include two servic colleagues of mine, have stated that, based on their personal experiences, it is possible significantly improve the performance of any health system, even in a relativel unfavourable environment of governance, given good leadership and support.
Keywords: Tuberculosis